Improving English pronunciation students through drilling technique at SDS Pelangi School - Theodesia Lady Pratiwi; Angel Rosinta Uli Simorangkir (Journal of English Language and Pedagogy, 2022)
This study aims to improve English pronunciation students through drilling techniques in English subject for 3rd-grade students at SDS Pelangi School. The subjects of this study were 9 which is 3rd-grade students. The instruments used are an observation field note and test and an interview. The study method used is Classroom Action Research. Starting from the problems experienced by students in English pronunciation at SDS Pelangi School are still low. Responding to existing problems, the right technique to improve students' English pronunciation is to use drilling techniques. This study was conducted in two cycles and the result showed there was also a significant increase in students' pronunciation. The average score of students from Cycle II increased by 10.34 from Cycle I. It can be said that the use of the drilling technique can improve student English pronunciation. Keywords: Pronunciation, Drilling Technique, Teaching Pronunciation to EYL